The Contribution of The Constitutional Law of The Banggai Kingdom to The Practice of State Administration in Indonesia - Sahran Raden; Hamiyuddin; Amir Basari Zanki (As-Siyasi: Journal of Constitutional Law, 2026)
This article examines the contribution of the customary constitutional law of the Banggai Kingdom to contemporary constitutional practices in Indonesia. While previous studies on customary law have primarily focused on civil, criminal, and administrative aspects, limited attention has been given to customary constitutional law as a framework of governance. This study addresses that gap by analyzing the institutional structure and governing principles of the Banggai Kingdom using the theoretical framework of trias politica, checks and balances, and decentralization within a unitary state. This study employs a normative legal research approach using statutory, conceptual, and historical approaches. The analysis is conducted through a systematic examination of legal texts, historical records, and relevant scholarly literature to interpret the structure, functions, and authority of customary institutions in the Banggai Kingdom. The findings reveal that the Banggai Kingdom developed a governance system reflecting a functional distribution of powers that parallels modern constitutional principles. The King (Tomundo) exercised executive authority, while Basalo Sangkap Sangkap functioned not only as a legislative body but also as a mechanism of checks and balances through its authority to deliberate, elect, and supervise the ruler. This demonstrates an early form of separation of powers and participatory governance embedded within customary institutions. This study contributes theoretically by advancing the concept of indigenous constitutionalism as an analytical framework for understanding non-Western constitutional traditions. Practically, it provides insights into how customary governance models can inform contemporary policies on regional autonomy, democratic governance, and institutional balance in Indonesia.